2019
DOI: 10.1111/aen.12440
|View full text |Cite
|
Sign up to set email alerts
|

Sex ratio and female allocation to harems in a polygynous bark beetle

Abstract: Varying forms of polygyny are observed across many animal groups. In some species, groups of females may remain with a single male for an extended length of time. This is often referred to as harem polygyny. A female‐biased sex ratio has been associated with harem polygynous species. In such species, formation of harems may be an inevitable consequence of the relative lack of available males, rather than multiple females actively choosing to mate with a subset of specific males. The five‐spined bark beetle, Ip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…For Ips acuminatus , the number of females per nuptial chamber was also found to range from 1 to 5 (Bakke, 1968). The sex ratio of Ips and the degree of monogamy versus polygamy may differ depending on environmental conditions (Bakke, 1968; Griffin et al., 2020). We speculate that the sex ratio of SI adults may be affected by both the interior and exterior environmental conditions of host trees.…”
Section: Discussionmentioning
confidence: 99%
“…For Ips acuminatus , the number of females per nuptial chamber was also found to range from 1 to 5 (Bakke, 1968). The sex ratio of Ips and the degree of monogamy versus polygamy may differ depending on environmental conditions (Bakke, 1968; Griffin et al., 2020). We speculate that the sex ratio of SI adults may be affected by both the interior and exterior environmental conditions of host trees.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, females may trade off costs of dispersal with staying at the first log they land on and the increased costs of breeding at high densities [ 19 ]. Previous studies of I. grandicollis have indicated that females choose males at random and do not select on the basis of quality of the male (e.g., male size) or the number of females already associated with the male [ 18 , 48 , 49 ]. Random selection of bore holes may be a consequence of predator avoidance by females by selecting the first available hole that they encounter [ 17 ].…”
Section: Discussionmentioning
confidence: 99%